PENINGKATAN KETAHANAN KELUARGA MELALUI OPTIMALISASI PERAN JAMAAH MUSLIMAH DI MASJID RAYA AL-MUHAJIRIN KABUPATEN BEKASI - Fahrany, Sofia; Yasin, Rahman; Sirojuddin, Sirojuddin (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
In recent years, Indonesia has experienced a decline in morals, akhlakul madzmumah (despicable morals), a decline in the quality of good behavior due to lack of parental supervision and the influence of gadgets, online media that can be accessed, with any livelihood in the palm of your hand. The rise in cases of delinquency and crime such as cases of drug abuse, and sexual deviations among lesbians, gays, bisexuals and transgender people, where sexually transmitted diseases are transmitted. According to data from the National Narcotics Agency, as many as 2.2 million Indonesian teenagers are drug abusers, according to Imelda to Radio Republik Indonesia on Wednesday, June 26 2024. . Indonesia has a population of 3% LGBT. In other words, of the 250 million Indonesian population, around 7.5 million of whom are LGBT due to parental negligence in educating their children, meaning that out of 100 people gathered, 3 of them are LGBT (CIA research reported by sixpackmagazinedotnet, research by Hasnah journal of the Nursing Study Program, FKIK UIN Alaudi Makasar). Family in Arabic is called ahlun from ahal which means marriage, apart from the word ahlun the words which mean family are, asyirah (family of descendants), and qurba (those related to kinship). Home and family are the main basis for religious education from an early age which is usually carried out by the mother (Al-Ummu Madrasatul “Ula). As Rasulullah SAW said,